Investigating Writing Instruction Practices for Students With Deafness and Hearing Loss - Dunn, Michael; Albagshi, Amira; Aldawsari, Faisal (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
This case study investigated the writing instruction practices of teachers (grades 6 and 7) of students with deafness and hearing loss. The researchers focused on what classroom practices and strategies teachers employed with students, what teachers’ perspectives were about best-practices for writing instruction, students’ perspectives about writing, and scores from their end-of-unit writing samples. The authors completed qualitative interviews and classroom observations with teachers (N=2) and students (N=6; three per class observed) about writing instruction for students with deafness and hearing loss. The data resulted in four themes: the need for teacher modeling, guided practice, and developing students’ independence; students’ challenges with writing (e.g., from ASL to English prose); the need for more resources (e.g., professional development about writing); and how assessment helps define students’ strengths and weaknesses.